Correction to: ZGLS: a novel flat quorum-based and reliable location management protocol for VANETs (Wireless Netw, (2018), 24, (1885â1903), 10.1007/s11276-016-1443-4) - Rehan, M. (2019)
The original version of this article contained an error in co-authorâs affiliation. The correct affiliation of Dr. Waqas Rehan is given in this erratum. Â© 2018, Springer Science+Business Media, LLC, part of Springer Nature.